Comprehensive Examination of Health Technology Assessment in Policy Formulation and Implementation - Almotah, Sultan Abdulaziz A; Al Nasser, Ali Nasser; Nahari, Ali Mohammed Ali; Alabsi, Doaa Salim Hamid; Mobarky, Weam Ali Esmael; Albakri, Abdullah Ahmed Abdulrazaq; Alnaser, Khalid Naser Naser; Alzahrani, Mohammed Murzi Asiri; Alalhareth, Hussain Mudshil; AlNasser, Hussein Nasser Nasser (Journal of Ecohumanism, 2024)
Health Technology Assessment, or HTA, is conceived as a key instrument to assess the clinical efficacy or efficiency and social impact of specific health technologies for policy purposes. This paper discusses incorporating HTA information in formulating and implementing policies focusing on the rational use of resources in healthcare systems. This study provides an understanding of the global case studies of HTA to outline the problem areas, advantages, and developments in the context of decision-making for health. The paper underscores seven evidence-based ways stakeholder involvement, methodological practices, and intersectoral cooperation create value in HTA.